Combination treatment of rituximab and donor platelets infusion to reduce donor‐specific anti‐HLA antibodies for stem cells engraftment in haploidentical transplantation. Issue 7 (28th February 2020) - Zhang, Rongli; He, Yi; Yang, Donglin; Jiang, Erlie; Ma, Qiaoling; Pang, Aiming; Zhai, Weihua; Wei, Jialin; Feng, Sizhou; Han, Mingzhe
Abstract: Background: Donor‐specific anti‐human leukocyte antigen (HLA) antibodies (DSAs) in recipients is a risk factor for donor stem cell graft failure in haploidentical hematopoietic stem cell transplantation (haplo‐HSCT), and the treatment to reduce the levels of DSAs is not unanimous. This study was to analysis the role of DSAs for stem cell engraftment and to discuss the effective treatment to reduce DSAs in haplo‐HSCT. Methods: We retrospectively evaluated the levels of DSAs and the effect of the combination treatment of rituximab and donor platelets (PLTs) for donor stem cell engraftment in haplo‐HSCT patients from June 2016 to March 2018 at our center. Results: Nine patients (11.5%) out of the total 78 patients were DSAs‐positive and multivariate analysis revealed DSAs was the only factor that affected engraftment. Seven out of the 9 DSAs (+) patients received therapy: Four had antibodies against donor HLA class I (HLA‐I) antigens and were administered two therapeutic amounts of donor apheresis platelets (platelet count approximately 3‐5 × 10 11 ) before donor stem cell infusion and the other three patients received a combination therapy of donor apheresis platelets and rituximab due to the antibodies against both donor HLA‐I antigens and HLA class II (HLA‐II) antigens. All the seven patients achieved donor stem cell engraftment successfully, and the DSAs levels decreased rapidly after transplantation. Conclusions: DSAs is an important factor affecting engraftment in haplo‐HSCT. Donor platelet transfusion is one simple and effective treatment for HLA‐I DSAs, and a combination therapy should be administered if patients have both HLA‐I and HLA‐II antibodies.